Stany sprężyste podczas zmian fazowych - Madejski, J. (Engineering Transactions, 1969)
Elastic states created by phase changes are analyzed by the proposed linear theory, Examples of a spherical reservoir and a thick-walled tube are given and the coexistence of stresses caused l temperature variations and phase transformations discussed. The importance of states of stress and strain created by nuclear radiation-induced phase changes is emphasized.